ENGLISH GRAMMATICAL COMPETENCE OF AMONDUS IN SECOND LANGUAGE ACQUISITION - Yanuarius Seran; Joni Soleman Nalenan (University of Muhammadiyah Malang, 2022)
Second language (L2) occurs when an individual has acquired firstlanguage (L1) and commonly acquired through scientific and naturalways. Second language acquisition generally takes place at younger ageand through formal and nonformal education. Amondus, the participant ofthis study, confirmed that he started to learn and acquire English as hissecond language at his adulthood. Having started to learn English in highschool, he just found it interesting and important during his college time.He found many English terms in his major, nursing. This reason led him toput his extensive effort in learning English. This qualitative descriptivecase study aims at investigating Amondus’ grammatical competence in hissecond language acquisition. Semi-structured and extensive interviewswere used to collect the data before they were analyzed throughtranscription, investigation and classification, analysis, and conclusiondrawing. The results showed that Amondus has possessed and masterednine grammatical morphemes, despite a minor error related to the use ofcopula that was still contextually understandable. Amondus’ oralgrammatical competence related to nine grammatical morphemes wasconsidered effective.